2012
DOI: 10.1097/sih.0b013e318266d0c6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Inexpensive Vaginal Hysterectomy Simulator

Abstract: This technical report details the construction of a vaginal hysterectomy simulator, the individual parts, the cost of each part, and the results of a blinded survey of resident physicians who used the simulator during their vaginal hysterectomy instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Recent literature contains suggestions for improving education through simulation models (22), objectively evaluating vaginal surgical skills (23), and techniques to address a difficult hysterectomy (24). Another way to improve trainee experience is to increase vaginal hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature contains suggestions for improving education through simulation models (22), objectively evaluating vaginal surgical skills (23), and techniques to address a difficult hysterectomy (24). Another way to improve trainee experience is to increase vaginal hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies assessing the transferability of laparoscopic and endoscopic simulators to real-time performance have proved to be useful of simulatorbased training (14,15,18,19). A VH simulator has been shown to have beneficial effects in learning routine VH (20,21). Although Greer et al (21) have shown that structured multiplecomponent VH education is valid, the impact of VH simulation on surgical competence could be unproven.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal hysterectomy was taken to be more difficult for other indications because of severe pelvic adhesions frequently seen in Nigerian women requiring hysterectomy, low surgical experience and expertise, and reduced exposure of residents in surgical competence in virtually all the centres in Nigeria [27,28,29]. Complex anatomy of the pelvis and technical challenge contribute to a steep curve for inexperienced surgeons [30]. Most centres hardly do up to five vaginal hysterectomies in a year.…”
Section: Indicationsmentioning
confidence: 99%